ANALISIS RASIO KETERGANTUNGAN DAN TINGKAT PENGANGGURAN TERBUKA TERHADAP INDEKS PEMBANGUNAN MANUSIADI PROVINSI ACEH - Nurul Shalihah; Hijri Juliansyah; Mutia Rahmah (LPPM UNIMAL, 2021)
This study examined the effect of dependency ratio and unemployment rate on the human development index in Aceh Province. This study used secondary data with the type of time series data during 2002-2020 obtained from the Central Bureau of Statistics. The data analysis method used was Vector Auto Regression (VAR). The results showed that the HDI did not have a negative and significant effect on themselves, ABK had no negative and significant effect on the HDI, and TPT had no negative and significant effect on the HDI.